2017
DOI: 10.1111/zph.12411
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of Leptospira infection in Mediterranean periurban micromammals

Abstract: SummaryUrbanization of natural areas can change abiotic factors, providing artificial sources of humidity in summer and decreasing variation of temperatures in winter. Our study aimed at document risk factors of infection in mammal reservoirs of pathogenic Leptospira in the human/wildlife interface of a large metropolitan area. We hypothesize that survival of Leptospira and thus their prevalence in animal reservoirs should be higher in residential areas than in natural habitats, especially after the hot, dry M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“…To our knowledge, this is the first study in Spain to confirm by MAT, the seropositivity against serovars Bataviae, Bratislava, Cynopteri, Grippotyphosa, Pomona, Proechimys, and Rachmati in cats, suggesting the possible presence of serovars from serogroups Australis, Autumnalis, Bataviae, Cynopteri, Grippotyphosa, and Pomona among cats in the country. In the metropolitan area of Barcelona, Spain, the presence of members of serogroups Australis, Bataviae, and Grippotyphosa (also detected in our study in cats) has been detected in small mammals [40], so it may be possible for serovars to circulate between animal species. Another factor to consider is the increased contact between cats and animal reservoirs of leptospires, due to shifts in the dynamics and colonization of cities.…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, this is the first study in Spain to confirm by MAT, the seropositivity against serovars Bataviae, Bratislava, Cynopteri, Grippotyphosa, Pomona, Proechimys, and Rachmati in cats, suggesting the possible presence of serovars from serogroups Australis, Autumnalis, Bataviae, Cynopteri, Grippotyphosa, and Pomona among cats in the country. In the metropolitan area of Barcelona, Spain, the presence of members of serogroups Australis, Bataviae, and Grippotyphosa (also detected in our study in cats) has been detected in small mammals [40], so it may be possible for serovars to circulate between animal species. Another factor to consider is the increased contact between cats and animal reservoirs of leptospires, due to shifts in the dynamics and colonization of cities.…”
Section: Discussionsupporting
confidence: 68%
“…Infected bovines also constitute an active reservoir for the spread of the zoonotic disease, especially for humans in direct contact with infected animals including veterinarians, abattoir and farm workers, hunters, as well as scientists handling laboratory animals or during fieldwork [ 3 , 4 ]. Domestic and wild animals are important reservoirs in rural areas, unlike urban settings where rats play a major dissemination role [ 5 , 6 ]. Human infection with Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Derne et al [116] tested the dilution effect hypothesis on the prevalence in human beings at a global scale. The other studies all tested the effect of wild hosts-related exposures on the infection in wild hosts, but these exposures were very heterogeneous: proximity with fruit bats [117], composition of rat population [118], density of small mammals [119], and density of rodents [120]. As such any synthesis was not attempted.…”
Section: Animal Biodiversity-related Exposuresmentioning
confidence: 99%
“…Group 22 (density of cervids): Four studies were excluded from the synthesis as they were attributed a medium/low validity [120,133,138,139]. The three studies that tested the effect of deer density on the human incidence of Lyme disease found a positive correlation, but variable in time and in space.…”
Section: Animal Biodiversity-related Exposuresmentioning
confidence: 99%